Effects of Al-doping on the properties of Li-Mn-Ni-O cathode materials for Li-ion batteries: An ab initio study - Dianat, Arezoo; Seriani, Nicola; Bobeth, Manfred; Cuniberti, Gianaurelio (Giovanni) (Journal of Materials Chemistry A, 2013)
The key properties of a successful cathode material, such as the structural stability during delithiation, the battery voltage, and the Li mobility, were investigated for Al-doped Li-Mn-Ni oxide structures, using density-functional theory and the nudged-elastic band method. The rhombohedral layered structure of LiMn0.5Ni0.5O2 with zigzag and flower arrangements of transition metal atoms as well as the monoclinic structure of Li(Li1/6Ni1/6Mn2/3)O2 were used as base structures. A stabilizing effect of Al-doping was found for all partially lithiated systems considered. The derived battery voltages at zero temperature are generally enhanced by Al-doping. The calculated activation energies for Li jumps suggest slower Li mobility. The Al-doped Li-rich monoclinic structure seems to be most promising as a cathode material because of a comparatively high battery voltage. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20